Figurative Language as Used in the Selected Song Lyrics of Those Shocking Shaking Days V/A Album - Jati Widya Iswara; Ika Syelvy Rizqyani (Universitas Stikubank (UNISBANK) Semarang, 2021)
Literature consists of things such as song lyrics, narrative words, poetry, etc. Those things are reflected into figure of speech and figurative language to create for huge interpretation by audiences. Meanwhile, in this present study the researcher uses a various artist album in Those Shocking Shaking Days released by Now Again Record home based in Los Angeles, California. This paper presents a descriptive qualitative as method in obtain the data of figurative language in the selected songs of Those Shocking Shaking Days V/A album. The paper concludes about variety of figurative language in the selected song lyrics and the most frequently figure of speech used.